Is late diagnosis of lung cancer inevitable? Interview study of patients' recollections of symptoms before diagnosis. Issue 4 (24th March 2005) - Corner, J; Hopkinson, J; Fitzsimmons, D; Barclay, S; Muers, M
Abstract : Background: A study was undertaken to explore the pathway to diagnosis among a group of patients recently diagnosed with lung cancer. Methods: A directed interview study triangulating patients' accounts with hospital and GP records was performed with 22 men and women recently diagnosed with lung cancer at two cancer centres in the south and north of England. The main outcome measures were the symptoms leading up to a diagnosis of lung cancer and patient and GP responses before diagnosis. Results: Patients recalled having new symptoms for many months, typically over the year before their diagnosis, irrespective of their disease stage once diagnosed. Chest symptoms (cough, breathing changes, and pain in the chest) were common, as were systemic symptoms (fatigue/lethargy, weight loss and eating changes). Although symptoms were reported as being marked changes in health, these were not in the main (with the exception of haemoptysis) interpreted as serious by patients at the time and not acted on. Once the trigger for action occurred (the event that took patients to their GP or elsewhere in the healthcare system), events were relatively speedy and were faster for patients who presented via their GP than via other routes. Patients' beliefs about health changes that may indicate lung cancer appeared to have played a part in delay in diagnosis. Conclusion: Further investigation of the factors influencing the timing of diagnosis in lung cancer is warranted since it appears that patients did not readily attend GP surgeries with symptoms. Insight into patients' perspectives on their experience before diagnosis may help medical carers to recognise patients with lung cancer more easily so that they can refer them for diagnosis and treatment. Encouragement to present early with signs of lung cancer should be considered alongside other efforts to speed up diagnosis and treatment.